Improving the methods of shooting training of young biathletes - Bakhtiyor, I.; Rustam, M.; Maruf, O. (American Journal of Social and Humanitarian Research (AJSHR), 2022)
This article discusses the development of a method of training in shooting at idle for young biathletes. It will focus on the theoretical and methodological foundations of shooting training for young biathletes, as well as safety rules for handling weapons during training and methods of teaching shooting techniques. A comparative analysis of the low readiness of young biathletes to idle is presented.